Alignment between strategy and intellectual capital development - Noradiva Hamzah; Mohd. Nazari Ismail (Penerbit Universiti Kebangsaan Malaysia, 2007)
This study is aimed at providing both an empirical and theoretical link between strategic management and the three categories of intellectual capital (i.e. human capital. organizational capital and relational capital).This study investigates whether organization's intellectual capital development management reflects to the distinct requirements of its strategy. A case study approach was employed on a total of eight organizations of various industries. Data was collected through in-depth discussions, 'company tours' and collaborated with documents evidence shared during interviews. In analysing the data collected, this study carried out within-case analysis and cross-case analysis. The study found that the development and management of organization's intellectual capital is contingent upon the strategy employed by the organization. Thus, this study has demonstrated that there is a link between the intellectual capital management and organization s competitive strategy.